Surface site modulations by conjugated organic molecules to enhance visible light activity of ZnO nanostructures in photocatalytic water splitting - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Journal of Physical Chemistry C, 2015)
Surface modification of ZnO nanoparticles is identified as a method of modulating surface sites advantageously. ZnO nanoparticles of two different sizes are surface modified with a conjugated organic moiety to enable electron conduction and transfer. Enhanced H-2 evolution from water-methanol mixtures was observed in the composite systems compared to pristine ZnO under visible light irradiation without any cocatalyst. The system is also marginally active in water splitting in pure water without any sacrificial agents. Photophysical characterization indicates that even though reducing size into the nanoregime affects the band gap detrimentally, modifications by simple conjugated organic molecules assist in enhanced visible light activity. The experimental observations are corroborated with computational studies, which also point to a localization of valence band maximum of the interface on the organic moiety and conduction band minimum on ZnO.

Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

Nitrogen-doped graphene with a three-dimensional architecture assisted by carbon nitride tetrapods as an efficient metal-free electrocatalyst for hydrogen evolution - Gangadharan, Pranav K.; Unni, SreeKuttan M.; Kumar, Nandha; Ghosh, Prasenjit; Kurungot, Sreekumar (Chemelectrochem, 2017)
Current polymer membrane-based electrolyzers use Pt as a cathode catalyst for efficient reduction of water. The high cost of Pt-based catalysts forces researchers to develop alternative electrocatalysts. Here, a simple strategy has been proposed to synthesize a metal-free electrocatalyst for the hydrogen evolution reaction (HER) by high-temperature annealing of graphene oxide-coated melamine foam. The prepared catalyst possesses both structural and functional advantages with its three-dimensional (3D) interconnected arms of carbon nitride (CNx) backbone wrapped with nitrogen-doped graphene (N-RGO) sheets (CNx@N-RGO). CNx@N-RGO faces only a 193 mV overpotential to achieve a current density of 10mAcm(-2), which is far superior to the previously reported Pt-free systems. Along with the high exchange current density 34.7 x 10(-6)A cm(-2) and low Tafel slope of 54 mV dec(-1), CNx@N-RGO follows a Volmer-Heyrovsky mechanism for the HER. DFT calculations show that the synergy between CNx and N-RGO facilitates good electrical coupling between the two moieties and provides optimal binding to H+ ions on the catalyst that, in turn, results in efficient reduction of hydrogen ions.
Keywords: carbon nitride; Density functional theory; electrocatalyst; hydrogen evolution reaction; nitrogen doped graphene

Sensitizing with short conjugated molecules: multimodal anchoring on ZnO nanoparticles for enhanced electron transfer characteristics, stability and H-2 evolution - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Catalysis Today, 2018)
Sensitizing semiconductors with organic dyes is usually employed to improve efficiency of semiconductors towards visible light absorption and charge transport. However, till date most of the dyes are either noble metal based with complex and expensive synthesis procedure or have a very narrow absorption band. Further the photostability of the dyes is another important issue. In this work we have studied, using a combination of photophysical and computational methods, ZnO nanoparticles sensitized with transition metal free, cheap and easy to synthesize azoquinoline dye that has been designed to have multiple chelating sites, viz., carboxylic group and hydroxyl imine group as a photocatalyst for water splitting activity. We find that the presence of multiple chelating sites facilitates dual mode of anchoring on ZnO nanoparticles, which leads to enhanced photostability and H-2 generation of the composite. This is attributed to the incorporation of resonance features in the dye that increases electron transfer between ZnO and dye in contrast to the charge accumulation and photo degradation observed in non-conjugated and single site anchoring counterparts. Electron transfer from ZnO to dye under UV light and reverse in visible light could be identified experimentally. Such simple designing aspects can aid in identifying better catalysts for photocatalytic water splitting.

Descriptors to predict dye-sensitized semiconductor based photocatalyst for hydrogen evolution reaction - Sappati, Subrahmanyam; George, Leena; Swamy, Vincent Paul; Devi, R. Nandini; Ghosh, Prasenjit (ChemCatChem, 2019)
Discovering efficient photocatalysts for hydrogen production from water splitting is highly desirable. Computational studies can help in rational designing of such catalysts through high throughput screening of materials. However, for that purpose one needs to identify descriptors that not only connects material properties with their functionality but are easy and inexpensive to compute. Using a combination of density functional theory based calculations and experiments we show two descriptors, namely, charge injection efficiency and electron hole separation, that can be used for in silico design of new and efficient dye-sensitized-semiconductor composites as catalysts for hydrogen evolution reaction.
Keywords: charge injection; descriptor; dye-sensitized semiconductors; electron-hole separation; H-2 evolution

Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol

Crystalline xylitol production from corncob biomass with oral toxicity analysis - Ahuja, Vishal; Dasgupta, Diptarka; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; More, Snehal; Gupta, Piyush; Behera, Babita; Bhaskar, Thallada (Industrial Crops and Products, 2022)
Xylitol, a five-carbon sugar alcohol, has a steady global market and finds application as a natural sugar substitute in various food and confectionery products. Biocatalytic xylitol production, although touted as a greener alternative to conventional chemical catalysis, suffers from certain challenges, the primary being high cost of production. This study demonstrates a process for food-grade xylitol production from corncob biomass with energy reduction through two major process modifications. A non-conventional fermentation strategy was adopted whereby adjusting aeration without agitation, xylitol with high yield (0.86 +/- 0.015 g/g), and productivity (0.74 gL(-1)h(-1)) could be produced by a GRAS Pichia caribbica MTCC 5703 strain. Xylitol was recovered from the broth in the form of crystals using a combination of membrane-based filtration and crystallization. The crystals demonstrated similar to 98 % purity when quantified with H-1 NMR. Oral toxicity analysis of the crystals demonstrated no adverse effect in female Winstar rats (at a loading of 2000 mg/kg body weight of animals). Overall process statistics showed that 0.584 kg of food-grade xylitol crystals could be produced from 3.5 kg of corncob biomass. The two-process modifications during fermentation and xylitol recovery enabled an energy saving of similar to 20.842 kW/kg of crystals, providing tremendous advantages for biorefinery-based large-scale xylitol production from corncob biomass.
Keywords: Biomass; Fermentation; Oral toxicity analysis; Wastewater treatment; xylitol

Process development for detoxification of corncob hydrolysate using activated charcoal for xylitol production - Ahuja, Vishal; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; Sarkar, Bipul; Sutar, Ajit; More, Snehal; Dasgupta, Diptarka (Journal of Environmental Chemical Engineering, 2022)
The work describes process development for detoxification of corncob hydrolysate using activated carbon for microbial xylitol production. Activated carbon was used as an adsorbent to completely remove the major fermentation inhibitors obtained during dilute acid and steam explosion of biomass. A xylitol yield of 0.78 g/g was achieved from the detoxified hydrolysate in a 5 L fermenter by Pichia caribbica. The spent carbon was effectively regenerated and used for three consecutive cycles of operation. The successive regeneration and reuse of carbon could reduce the operational cost by similar to 38% and be used as a reference dataset for process scale-up and cost-effective xylitol production.
Keywords: Activated charcoal; Detoxification; Fermentation; Regeneration; xylitol

Unusual ligand assistance in molecular electrocatalysis via interfacial proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Chame, Pallavi Vyankuram; Ghosh, Prasenjit; Vinod, Chathakudath Prabhakaran; Makri Nimbegondi Kotresh, Harish; Kanade, Sandeep C.; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2023)
We show that the ability of the ligand to reorganizethe electricdouble layer (EDL) often dominates the electrocatalysis contrary totheir inductive effect in the spectrochemical series, leading to counterintuitiveelectrocatalysis. With water oxidation and chlorine evolution as theprobe reactions, the same catalytic entity with carboxy functionalizedligand exhibited surprisingly higher electrochemical activity in comparisonto the aggressively electron-withdrawing nitro functionalized ligands,which is contrary to their actual location in the spectrochemicalseries. Spectroscopic and electrochemical analyses suggest the enrichmentof catalytically active species in the carboxy substituted ligandvia proton charge assembly in the EDL that in turn enhances the kineticsof the overall electrochemical process. This demonstration of lessobvious ligands becoming indispensable in electrocatalysis suggestsa blind designing of ligands solely based on their inductive effectshould be reconsidered as it will prevent the utilization of the maximumpotential of the molecule in electrocatalysis.